IMPACT OF ICT ON INVENTORY MANAGEMENT IN RETAIL SUPPLY CHAINS: A STUDY OF IOT AND AI APPLICATION - Muhammad Hashim Zia; Raafay Qasim; Ayaan Hassan (Spectrum of Engineering Sciences, 2025)
The retail sector is using information and communication technology (ICT) more and more to maximize inventory control. This study examines how ICT, especially Internet of Things (IoT) and Artificial Intelligence (AI), affects inventory management in retail supply networks. Objective: To study the use of IoT and artificial intelligence in stock management and its effect on retail supply chain efficiency. Methodology: Survey-based study using stratified random sampling for data gathering from 100 retail professionals taking part in the survey. With an emphasis on businesses that have incorporated Internet of Things and artificial intelligence in their inventory management systems, data were gathered from Retail companies in urban areas. Online survey questionnaire was used for data collection. Results: Following the deployment of IoT and artificial intelligence technology, the research discovered a 25% decrease in inventory costs, from 100,000 to 75,000. From 80% to 104%, the research showed a 30% increase in supply chain efficiency, therefore implying higher production and reduced operational costs. Better product availability and fewer stockouts increased consumer happiness by 20%, from 80% to 96%. Overstocking and stockouts were found to have fallen 15% from 20% to 5%. Conclusion: The use of artificial intelligence and IoT in inventory management could completely revolutionize retail supply chains. Retailers can optimize inventory levels, minimize costs, and improve customer satisfaction by means of these technologies, hence gaining a competitive edge in the industry.